Effects of Visual Art Based Activities for Social Skills Development of Children with Down Syndrome: https://doi.org/10.55966/assaj.2025.4.1.077 - Madeeha Fasahat (`, 2025)
This study is focused on the effect of visual art-based activities for the development of social skills in children with Down syndrome enrolled at a rehabilitation center Step to learn located in Rawalpindi Pakistan. Participants of this study is between the age of 8 to 11 year two boys and one girl. It is a qualitative case study, and an observation-based research method was used. The researcher designed five days art activities-based workshop, by borrowing the framework of Kolb’s experiential learning theory (ELT) to see the impact of these art activities on the development of their social skills. Primary Data of this research is collected in the form of photos and videos of the students during the workshop while participants were doing art activities and from semi-structured interviews of the institute’s principal and faculty members. The themes of the literature review are derived from the responses of interviews and common words or phrases are color-coded. Secondary data is collected by analyzing the previous work done by students and from their health records. To assess the workshop results, the researcher took help from Dr. Kathleen Quill’s developed social skills checklist and from the already designed social skill checklist of Step to learn and developed another checklist. The findings of the study showed that if children with Down syndrome do art-based activities in the group, they can easily learn many essential social skills to lead a more constructive and accomplished life. Art-based activities helped them improve their relationship with peers and educators and enabled them to cooperate, share, and help each other. Not only this, but they also showed very positive results regarding self-helping skills. Keywords: Art Intervention; Visual Art; Social Skills; Down Syndrome.